2014
DOI: 10.1016/j.bbamem.2013.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Entry of Newcastle Disease Virus into the host cell: Role of acidic pH and endocytosis

Abstract: Most paramyxoviruses enter the cell by direct fusion of the viral envelope with the plasma membrane. Our previous studies have shown the colocalization of Newcastle Disease Virus (NDV) with the early endosome marker EEA1 and the inhibition of NDV fusion by the caveolin-phosphorylating drug phorbol 12-myristate 13-acetate (PMA) prompted us to propose that NDV enters the cells via endocytosis. Here we show that the virus-cell fusion and cell-cell fusion promoted by NDV-F are increased by about 30% after brief ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 62 publications
4
25
0
1
Order By: Relevance
“…For example, Newcastle Disease Virus enters HeLa and ELL-0 cells via low pH-dependent endocytosis [25]. The role of pH in hMPV entry is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Newcastle Disease Virus enters HeLa and ELL-0 cells via low pH-dependent endocytosis [25]. The role of pH in hMPV entry is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Past work showed that HMPV, NiV, and RSV can use the endosomal pathway to enter cells 106108 . Low pH exposure increases NDV fusion and subsequent syncytia formation while, reciprocally, fusion decreases in the presence of pH-acidification inhibitors 109 . Consistent with these results, the stability of NDV F (assessed through fusion assays) decreases after exposure to low pH; F is more easily activated under these conditions 109 .…”
Section: Proposed Mechanisms Of Receptor Binding Protein and Fusiomentioning
confidence: 96%
“…Low pH exposure increases NDV fusion and subsequent syncytia formation while, reciprocally, fusion decreases in the presence of pH-acidification inhibitors 109 . Consistent with these results, the stability of NDV F (assessed through fusion assays) decreases after exposure to low pH; F is more easily activated under these conditions 109 . There may be an accessory pH-dependent pathway through the caveolin-mediated endocytosis for NDV.…”
Section: Proposed Mechanisms Of Receptor Binding Protein and Fusiomentioning
confidence: 96%
“…Pore formation follows hemifusion and results in mixing of both outer and inner leaflet membrane lipids with concomitant mixing of aqueous contents; it is measured by a reporter gene assay [26,27]. Pore expansion is the final stage, it leads to the formation of multinucleated giant cells, and it is measured by syncytium formation assay [24,38]. Six of the mutated F proteins (L257A, L271A, I299A, L271A-L278A, L271A-L285A, and L278A-L285A), which nearly lost their ability to form syncytia, directed less than 16.0% of the levels of pore formation of the wt F protein and exhibited a hemifusion activity almost similar to the negative control level, with the rate and extent of initial fusion below 9.5% of the wt F level.…”
Section: Discussionmentioning
confidence: 99%
“…Quantification of syncytia was accomplished by measuring the syncytia-covered area in 3 random fields and comparing this with the total area of the field. Areas were quantified using the analysis tool in Adobe Photoshop CS6 [24]. …”
Section: Methodsmentioning
confidence: 99%